Impact of Physical Exercise on Symptoms of Depression and Anxiety in Pre-adolescents: A Pilot Randomized Trial - Philippot, Arnaud; Meerschaut, Alexandre; Danneaux, Laura; Smal, Gauthier; Bleyenheuft, Yannick; De Volder, Anne G. (Frontiers in Psychology, 2019)
Aim The intensity of the most appropriate exercise to use in depressed youth is unclear due to differences in methodology and the lack of evidence documenting the effect of physical activity in children. Therefore, the authors of this study attempted to document the effectiveness of different training intensities to reduce symptoms of depression and anxiety in pre-teens. Methods The study included twenty-seven, randomly selected pre-adolescents (aged between 9–11 years of age) all of whom had Primary education. The participants were enrolled and, over a 5-week period, were subject to either intensive or low-to-moderate exercise programs four times a week. Psychological self-reports, as well as physical examinations, were conducted before and after such programs in blinded assessments. Psychological effects were considered the primary outcome, whilst physical condition was secondary. Results Four subjects were lost and twenty-three were analyzed. General linear model with 2 criteria revealed significant changes (p = 0.05) in trait anxiety symptoms over time in the low-to-moderate intensity group (LMIG). Within group changes followed a significant decrease in levels of anxiety (38.82 ± 2.20 to 33.36 ± 2.83, p = 0.004) and depression (10.36 ± 2.83 to 6.73 ± 1.88, p = 0.006) related symptoms amongst those in the LMIG. Interpretation This study indicated that depression and anxiety symptoms were reduced amongst a non-clinical sample of Primary educated pre-adolescents when they were subject to a low-to-moderate exercise program. The program focused on associating movement with pleasure, encouraged positive and non-competitive interactions between participants. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT02970825, autumn 2016, updated May 7, 2018 (https://clinicaltrials.gov/ct2/show/NCT02970825).